DIVERSITY OF ECHINODERMS (ECHINODERMATA) IN THE NORTH EASTERN ISLANDS, VIETNAM - Thung, Do Cong; Dong, Dao Minh (Vietnam Journal of Marine Science and Technology, 2018)
41 species have been identified, belonging to 29 genera, 18 families, 10 orders and 5 classes of Echinoderms in Northeast islands, from Mong Cai (Quang Ninh) to Do Son (Hai Phong). Compared to previous publications, 15 species were first identified in the Tonkin Gulf. The diversity of species numbers shows that Oreasteridae and Holothuriidae have the highest number of species (5 species/family), similarly the genus Holothuri has the highest species number (5 species). Ha Long Bay - Cat Ba has 33 species; Co To - Thanh Lan has 24 species and Bai Tu Long has 25 species. Echinoderms live in three habitats: Sand, coral, reef. The highest number of species is living in the sandy bottom and coral reefs, 39% and the lowest number only about 10% in coral reefs and reef. Van Boi, Van Ha, Da Den, Bac Van, Hong Van have high density of Echinoderms, potentially becoming marine medicine yards.